Effect of ovarian functions on estrus sychronization and pregnancy rate in brown swiss heifers and non-lactating cows - Mehmet Köse; Tevfik Tekeli (Eurasian Journal of Veterinary Sciences)
Aim: In this study, the effect of ovarian functions on estrus synchronization and pregnancy rates in Brown Swiss heifers and non-lactating cows synchronized with a modified ovsynch protocol was investigated. Materials and Methods: The estrous cycle of heifers (n=60) and cows (n=27) was synchronized with two injections of 150 mcg d-cloprostenol (PGF2α) 14 days apart. Ovulation was induced with the injection of 50 mcg lesirelin acetate (GnRH) at 48 hour after the second PGF2α, and insemination (AI) was performed between 16-20 h following the last injection. Corpus luteum and follicle diameters were measured on days of PGF2α and GnRH injection with ultrasound. Moreover, blood samples were collected to assess plasma progesterone concentration on days of PGF2α injection and on AI day (day 0) and subsequently on 7, 14 and 21 days. Pregnancy was checked on day 28 after AI. Results: Synchronization and pregnancy rates were found 87.4% and 36.8%, respectively. The most important factor reducing the efficacy of protocol during synchronization period was no luteal function in 6.89% of cows at time of the second PGF2α injection. The affecting negatively on pregnancy rates in synchronized cows was determined two main factors. 1- Lack of luteal function on day 7 post-insemination (11.84% of synchronized). 2- Possible early embryonic deaths (11.84% of synchronized). Conclusions: It was concluded that the ovulation can be synchronized with modified ovsynch protocol, consisting of two PGF2α and one GnRH injection, and could be achieved to acceptable pregnancy rate in Brown Swiss heifers and non-lactating cows.